The Role of Law in Dealing Psychological Conflict Due to Breakup - Erni Susanty Tahir; Puput Mulyono (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
Breakups often trigger psychological conflict ranging from stress, anxiety, depression, to risky behavior that have an impact on individual well-being and the social environment. This study explores the role of law in preventing, responding to, and recovering such psychological impacts through an interdisciplinary approach. The methodology used is a normative-juridical study combined with a literature review of clinical psychology and mental health policy. The findings show that the legal framework can function on three levels: (1) preventive, through the guarantee of the right to mental health, digital literacy, and platform governance to prevent post-breakup online harassment; (2) protective, through victim protection mechanisms against psychological violence, stalking, doxing, and the dissemination of non-consensual intimate content; and (3) curative, with a referral scheme for counseling services, the provision of legal aid, data confidentiality guarantees, and restorative justice instruments centered on victim recovery. However, there are implementation gaps, including the lack of standardization of psychological assessments in the legal process, limited access to services at the grassroots level, and coordination between institutions that are not optimal. This article recommends the integration of mental health protocols in the law enforcement process, evidentiary guidelines for psychological violence, as well as cross-sectoral collaboration with psychological service providers and digital platforms. The main contribution of this study is the mapping of a comprehensive legal intervention framework for post-breakup psychological conflicts.